Validation of ELISA for Quantitation of Artemisinin-Based Antimalarial Drugs - Wang, Min (The American Society of Tropical Medicine and Hygiene, 2013)
The circulation of counterfeit or substandard artemisinins (ARTs) in malaria-endemic areas poses a serious threat to the long-term use of these drugs. Here, we validated an indirect competitive enzyme-linked immunosorbent assay (icELISA) for quantification of ARTs and found that 50% of inhibitory concentrations of dihydroartemisinin, artemether, and artesunate were 8.1, 207.0, and 4.7 ng/mL, respectively. We compared the icELISA with high-performance liquid chromatography (HPLC) for quantifying ART and its derivatives in 22 convenience samples of commercial antimalarial drugs. Paired t tests showed a borderline significant difference between the two methods (mean = 0.03, 95% confidence interval [CI] 0.00–0.07, P = 0.074) and the icELISA results were more variable than those of the HPLC analysis (P < 0.001), suggesting that further improvement is needed to enhance the performance of the icELISA. Our results showed that the icELISA has the potential to be improved for quality assurance of ARTs at the point of care in endemic settings.